Software Requirements Profile Quality Model - Gordieiev, Oleksandr; Kharchenko, Vyacheslav; Gordieieva, Daria (International Journal of Computing, 2022)
Article opens series of works devoted to profile-oriented software quality assessment. In this article the concept of software requirements profiling for subsequent software requirements profile quality assessment is analyzed and developed. The main result of the article is the development of the software requirements profile quality model. The model describes the following: characteristics and attributes of software requirements and their classification features; characteristics and attributes of software requirements profile and their classification features; semantics and syntax of software requirements. The article is based on analysis and use of the following standards: ISO/IEC 25012:2008, ISO/IEC/IEEE 29148:2018, ISO/IEC/IEEE 29148:2011. Examples of software requirements profile quality model are introduced. The suggested approach is used for the development of terms of reference or draft of a new standard. For example, the model is used for an assessment draft of the new standard “Requirements to computer security of NPP Instrumentation and Control Systems (NPP I&C)” developed by the Ukrainian state regulatory body. As a result of the development of the software requirements profile quality model, a set of propositions for improving the quality of the standard as a branch of the profile for NPP I&C cybersecurity are implemented.